Analysis of Situational Awareness for Online Taxibike Driver in Yogyakarta Using QUASA Analysis - Farid Ma'ruf; Hapsoro Agung Jatmiko (Jurnal Ilmiah Teknik Industri, 2020)
Online taxibike servicehas its own charm because it is a new breakthrough for current conditions that make it easy for consumers to order a vehicle. Riding a motorcycle is an activity that requires awareness against road conditions that are dynamic and can change in seconds. This study aims to determine the level of awareness of online taxibikedriver when using a GPS and non GPS. The method used in this research is the QUASA method which combines the probing method in the situational awareness process with the self rating method. The results of data processing obtained that the value of actual accuracy and perceived accuracy when online taxibikedriver uses a GPS is greater than non GPS. In addition, other results stated that the level of awareness of online taxibikedriver when using a GPS was 4.7% greater than when without non GPS.